PI3K signalling - Martin Turner (Frontiers Research Topics, 2015)
The PI3Ks control many key functions in immune cells. PI3Ks phosphorylate PtdIns(4,5)P2 to yield PtdIns(3,4,5)P3. Initially, PI3K inhibitors such as Wortmannin, LY294002 and Rapamycin were used to establish a central role for Pi3K pathway in immune cells. Considerable progress in understanding the role of this pathway in cells of the immune system has been made in recent years, starting with analysis of various PI3K and Pten knockout mice and subsequently mTOR and Foxo knockout mice. Together, these experiments have revealed how PI3Ks control B cell and T cell development, T helper cell differentiation, regulatory T cell development and function, B cell and T cell trafficking, immunoglobulin class switching and much, much more. The PI3Kd inhibitor idelalisib has recently been approved for the treatment of B cell lymphoma. Clinical trials of other PI3K inhibitors in autoimmune and inflammatory diseases are also in progress. This is an opportune time to consider a Research Topic considering when what we have learned about the PI3K signalling module in lymphocyte biology and how this is making an impact on clinical immunology and haematology.